2018
DOI: 10.1158/0008-5472.can-17-3199
|View full text |Cite
|
Sign up to set email alerts
|

The Canonical Wnt Pathway Drives Macropinocytosis in Cancer

Abstract: Macropinocytosis has emerged as an important pathway of protein acquisition in cancer cells, particularly in tumors with activated Ras such as pancreatic and colon cancer. Macropinocytosis is also the route of entry of Bacillus Calmette-Guerin (BCG) and other microbial therapies of cancer. Despite this important role in tumor biology and therapy, the full mechanisms by which cancer cells can activate macropinocytosis remain incompletely defined. Using BCG uptake to assay macropinocytosis, we executed a genome-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 50 publications
(74 reference statements)
7
95
0
Order By: Relevance
“…We demonstrate that RIN1 is a significant regulator of macropinocytosis, a process which has recently been specifically associated with RAS activation ( Figure 2B,C) (22,23). These observations establish a mechanistic link between RAS and macropinocytosis and provide a context for more detailed screening (45).…”
Section: Deep Ppi Network Illuminate New Facets Of Ras Pathway Biologysupporting
confidence: 61%
“…We demonstrate that RIN1 is a significant regulator of macropinocytosis, a process which has recently been specifically associated with RAS activation ( Figure 2B,C) (22,23). These observations establish a mechanistic link between RAS and macropinocytosis and provide a context for more detailed screening (45).…”
Section: Deep Ppi Network Illuminate New Facets Of Ras Pathway Biologysupporting
confidence: 61%
“…Previous studies have shown that macropinocytosis is one mechanism whereby cancer cells scavenge nutrients from the microenvironment to support survival and proliferation (Commisso et al, 2013;Davidson et al, 2017;Hodakoski et al, 2019;Kamphorst et al, 2015;Kim et al, 2018;Lee et al, 2019;Palm, 2019;Palm et al, 2017;Recouvreux and Commisso, 2017;Redelman-Sidi et al, 2018;Yao et al, 2019;Zhang and Commisso, 2019). Due to its large size, fluorescently-labeled dextran is used as a surrogate for macropinocytosis as it cannot be taken up through other endocytic pathways Ivanov, 2008).…”
Section: Inhibition Of Atm Kinase Activity Induces Macropinocytosis Tmentioning
confidence: 99%
“…Next we aimed to determine the mechanism of macropinocytosis induction downstream of ATM inhibition. Towards this goal, we used pharmacological or genetic inhibition of PI3K/AKT, WNT, and AMPK, three known inducers of macropinocytosis (Commisso et al, 2013;Kim et al, 2018;Redelman-Sidi et al, 2018;Tejeda-Munoz et al). While inhibition of PI3K, AKT, or WNT had no effect ( Fig.…”
Section: Inhibition Of Atm Kinase Activity Induces Macropinocytosis Tmentioning
confidence: 99%
See 2 more Smart Citations